2000
DOI: 10.1111/j.1540-8167.2000.tb00339.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific Up‐Regulation of Mitochondrial F0F1‐ATPase Activity after Short Episodes of Atrial Fibrillation in Sheep

Abstract: Specific activation of F0F1-ATPase activity is an early molecular consequence of sustained AF in sheep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…In addition, it has been proposed that complex I plays an essential role in the assembly of respirasomes that bring together ETC subunits, providing structural interdependence to the individual OXPHOS complexes important in channeling electron flow, controlling superoxide production (13,38), and sensitivity of mitochondria toward mitochondrial permeability transition pore opening (28). Alterations in expression of genes and protein subunits of complex I lead to disassembly, instability of the complex, and an increase in reactive oxygen species (ROS) production, thus resulting in cardiac diseases, cardiomyopathy (7,18), and heart failure (28). The BN-PAGE data indicate no difference in mobility of the complexes, suggesting that the structure of the complexes is not altered and a selective reduction in complex I and II activity might be due to other alterations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been proposed that complex I plays an essential role in the assembly of respirasomes that bring together ETC subunits, providing structural interdependence to the individual OXPHOS complexes important in channeling electron flow, controlling superoxide production (13,38), and sensitivity of mitochondria toward mitochondrial permeability transition pore opening (28). Alterations in expression of genes and protein subunits of complex I lead to disassembly, instability of the complex, and an increase in reactive oxygen species (ROS) production, thus resulting in cardiac diseases, cardiomyopathy (7,18), and heart failure (28). The BN-PAGE data indicate no difference in mobility of the complexes, suggesting that the structure of the complexes is not altered and a selective reduction in complex I and II activity might be due to other alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, direct and indirect evidence suggest that the activity of these two pumps might have been modified in our model. First, Barbey et al (12) have shown an increased activity of F 0 F 1 -ATPase but in absence of any change in Na,K-ATPase activity (7). On the other hand, the work by Songu-Mize et al (33) has shown increased Na pump activity by short term cyclic stretch in aortic smooth muscle cells.…”
Section: Af Energeticsmentioning
confidence: 94%
“…While ionic remodeling (3)(4)(5) as well as changes in cellular and structural architecture (6) have been described, increasing evidence for a role of perturbations in energetic metabolism exists. In fact, various studies have shown modifications in energetic metabolism in both animal models (7)(8)(9)(10)(11) and humans (12)(13)(14) and after both chronic or short episodes of AF (9,10,(12)(13)(14). However, a variety of changes have been observed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations